A Study of Resolution Improvement in Noncoherent Optical Coherence Imaging - Guoliang Yang; Junhong Su; Yuan Li; Jialin Cai; Yiren Li (Advances in Mathematical Physics)
Noncoherent light, as a common light source in life, can effectively avoid problems such as scattering noise caused by optical components incoherent light imaging, and through the design of the optical path can also trigger interference and holographic imaging of objects, allowing holography to be used in more fields. Various techniques have emerged for recording holograms using incoherent light sources as technology has developed. A recording method has been proposed that exploits the correlation between the object wave information and the Fresnel band sheet to achieve incoherent hologram recording. Using a spatial light modulator (SLM) loaded with a bit-phase mask with multiplexed lens function, the incident light wavefield is phase-modulated to achieve diffraction spectroscopy and phase shifting. And holograms with different phase shifts can be obtained and combined with phase-shifting techniques to eliminate the effects of twin images caused by coaxial holography in the reproduction process. Based on the study of this incoherent holographic imaging system, the influence of the characteristics of the main components of the system and the corresponding parameters on the resolution of the recorded and reproduced holograms is investigated, and optimization methods are given from both theoretical and experimental studies. The empirical analysis of the FINCH imaging system is carried out. The observed optical path is designed, and the method of making a bit-phase mask loaded on a spatial light modulator is presented. The effect of the focal length and recording distance of the dislocation mask on the resolution of the system is investigated by both computer simulation and experimental operation.